Appraisal of Cluster Front Line Demonstration on Rapeseed and Mustard in Bihar and Jharkhand - Kumar, Anjani; Kumar, Amrendra; Jha, Sudeepa Kumari; Singh, Sumit Kumar (Indian Journal of Extension Education, 2021)
Performance of ten varieties of rapeseed and mustard were assessed through cluster front line demonstration (CFLD) under different agro-climatic condition of Bihar and Jharkhand continuously for four years (2017-18 to 2020-21) by the KVKs of Bihar and Jharkhand. Among the agro-climatic zones of Bihar, highest yield was recorded in the demonstrated plot from zone III (B) i.e. South-West alluvial plain in case of variety RH 0749 (15.29 q/ha) and in Jharkhand state from zone I (Central and North astern plateau) with variety NRCHB 101 (13.31 q/ha). Lowest technology index was observed for variety Rajendra Sufalam in all the zone (-4.96, 5.53, 7.18 and 22.92 % in zone I, III (B), III (A) & II) of Bihar and NRCHB 101 (23.15 % in zone I) in Jharkhand. The range of extension gap was1.38 to 4.37 and 1.13 to 4.86 q/ha under the agro-climatic zone of Bihar and Jharkhand, respectively. Pooled data shows that in Bihar, maximum net return (Rs. 46986 /ha) was obtained in variety Rajendra Sufalam in agro-climatic zone III A of Bihar with benefit cost ratio 3.85:1 whereas under agro-climatic condition of Jharkhand maximum net return (Rs. 39598 /ha) was recoded from variety NRCHB 101 with benefit cost ratio 2.80:1.